2016
DOI: 10.1113/jp271694
|View full text |Cite
|
Sign up to set email alerts
|

The vaginal microbiota, host defence and reproductive physiology

Abstract: The interaction between the human host and the vaginal microbiota is highly dynamic. Major changes in the vaginal physiology and microbiota over a woman's lifetime are largely shaped by transitional periods such as puberty, menopause and pregnancy, while daily fluctuations in microbial composition observed through culture-independent studies are more likely to be the results of daily life activities and behaviours. The vaginal microbiota of reproductive-aged women is largely made up of at least five different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
267
1
22

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(300 citation statements)
references
References 140 publications
(125 reference statements)
10
267
1
22
Order By: Relevance
“…To assign Lactobacillus sequences to the species level, sequences were compared to the 16S Lactobacillus type strains downloaded from Bacterio.net. As was seen in previous studies [3, 9, 11, 39, 40] , many samples showed high proportions of bacteria from the genus Lactobacillus (Figure 1D–E). A total of 99.3% of Lactobacillus sequences were classified to the species level (using BLAST with e-value threshold of 10 −5 and percent identity > 97%).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…To assign Lactobacillus sequences to the species level, sequences were compared to the 16S Lactobacillus type strains downloaded from Bacterio.net. As was seen in previous studies [3, 9, 11, 39, 40] , many samples showed high proportions of bacteria from the genus Lactobacillus (Figure 1D–E). A total of 99.3% of Lactobacillus sequences were classified to the species level (using BLAST with e-value threshold of 10 −5 and percent identity > 97%).…”
Section: Resultssupporting
confidence: 85%
“…Diversity and pH were associated with Nugent score (Pearson’s correlation r=0.45 and r=0.44, p<0.001 and p<0.001 respectively, Supplemental Figure 2), paralleling several studies that have shown that BV is associated with low Lactobacillus , high diversity, and high pH [9, 11, 18, 39, 40] . The high diversity state was associated with increased representation of proinflammatory lineages (Figure 2G), including Mobiluncus .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…2011;DiGiulio et al 2015), an organism that has been associated with both health and disease (Macklaim et al 2011). Recent studies have shown that L. iners is associated with high diversity CSTs while L. crispatus (dominant species in CST I) is thought to be more protective against disease (Callahan et al 2017;Smith and Ravel 2017). We recovered 6 near complete L.…”
Section: Lactobacillus Genomes Vary In Their Mobile Elementsmentioning
confidence: 88%
“…The five reviews that follow fall into two groups. Three address the nature and physiological effects of microbiota outside the alimentary tract – the skin, vaginal canal and the oral cavity (authored by Barnard & Li (), Smith & Ravel () and Kumar (), respectively). The remaining articles focus on the gut microbiota, but rather than asking how this extensive microbial community influences digestive health and disease, they summarize evidence to support a role for the gut microbiota in regulating either systemic metabolism (Janssen & Kersten, ) or brain function (Dinan & Cryan, ).…”
Section: Physiological Effects Of Diverse Microbiotamentioning
confidence: 99%